Association of Novel Androgen Receptor Axis-Targeted Therapies With Diarrhea in Patients With Prostate Cancer: A Bayesian Network Analysis - Xiong, Xingyu; Xu, Hang; Wang, Sheng; Liao, Xinyang; Yi, Xianyanling; Jin, Kun; Lei, Haoran; Bai, Shengjiang; Qiu, Shi; Yang, Lu (Frontiers in Medicine, 2022)
Context: A paucity of research regarding the influence of novel androgen receptor axis-target (ARAT) agents on diarrhea and constipation. Objective: To perform a systematic review and network meta-analysis to characterize the effect of novel ARAT agents on diarrhea and constipation. Materials and Methods: We searched the Pubmed, Web of Science, and ClinicalTrials.gov up to September 2021 for phase 3 randomized controlled trials (RCTs) of patients receiving novel ARAT agents for prostate cancer (CaP). A Cochrane risk-of-bias tool was used to assess trial quality. The primary outcomes were risk ratio (RR) of any-grade diarrhea and constipation for patients receiving ARAT treatment. Relative risks of competing treatments were evaluated by pairwise and Bayesian network meta-analysis. Results: Thirteen trials with 15117 participants comparing 5 treatments (abiraterone, enzalutamide, apalutamide, darolutamide and placebo) were identified. Use of novel ARAT agents was associated a significantly increased risk of any-grade diarrhea (RR=1.30, 95%CI [1.16, 1.44]). As for subgroup analysis, abiraterone, enzalutamide and apalutamide were all associated significantly increased risk of any-grade diarrhea (Abiraterone: RR=1.40, 95%CI [1.09, 1.81]; Enzalutamide: RR=1.17, 95%CI [1.02, 1.35]; Apalutamide: RR=1.35, 95%CI [1.03, 1.76]). Based on Bayesian modeling, abiraterone and enzalutamide showed the highest and lowest probability to rank first in terms of increasing risk of any-grade diarrhea. There were no significant difference of risk in any-grade constipation, grade 3 or greater diarrhea and constipation between ARAT and control group. Conclusion: The present study indicates that the use of novel ARAT agents is associated with a significantly higher risk of diarrhea. Across the four agents, abiraterone may relate to the highest risk of diarrhea among patients with mHSPC and CRPC.